ANALISIS FENETIK TANAMAN KARET (Hevea brasiliensis (Willd. ex A. Juss) Mull. Arg.) BERDASARKAN PENANDA ISOZIM DI LIMA KABUPATEN SENTRA PERKEBUNAN KARET RIAU - Ivo Mayasari; Fitmawati '; Minarni ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Many kinds of rubber plants (Hevea brasiliensis (Willd. ex A. Juss) Mull. Arg.)has been cultivated in Riau Province. Phenetic analysis of rubber plants can giveinformation about their relationship. Study to obtain information about the relationshipamong rubber plants which are grown in 5 rubber plantation centers in Riau wasconducted based on isozyme markers. A total of 15 trees had been studied. The sampleswere taken from 5 regencies i.e. Bengkalis, Meranti, Kuantan Singingi, Kampar, andRokan Hulu using an exploration method. Four enzymes (PER, EST, ACP, and AAT)were used for similarity and clustering analysis using NTSys program version 2.02. Theresult of this research showed 19 polymorphic bands, 9 bands from PER, 5 bands fromEST, 2 bands from ACP, and 3 bands from AAT enzyme. The similarity analysis of 15individuals showed that the similarity coefficient ranged from 0.47-1. The clusteringresult showed that all of individuals were grouped at the coefficient of 0.59. Most of thesamples were grouped together based on the band similarity. However, all of samplescollected from Bengkalis, as well as Kuantan Singingi, formed a cluster due to the highband similarity.